SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMA NEGERI 28 KABUPATEN TANGERANG - Firdaus Juliarjo; Ahmad Fajrihim; Riki Rizki Ananda; Syaifur Rahmatullah Abdul Rojak (CV. Multi Kreasi Media, 2024)
The library is one of the facilities that must exist in schools aimed at supporting the process of teaching and learning activities for students at school. Currently the library information system that is currently running is still not well organized so that it is very influential in the process of managing library data whether it is recording new members, warehousing and returns that have not been computerized are still done manually, librarians must carry out all data collection processes both recording members new books, sales and returns on notebooks, it takes a long time to do all the library data management. The purpose of this final project research is to produce a web-based library information system application that is built using the waterfall model SDLC